ARAH KOMUNIKASI MASSA DALAM SISTEM MEDIA BERJARINGAN ONLINE (UKRI, 2023)
Media changes occurred in a revolutionary way. Its presence packaged in a new type of media replaces the existence and phases of old media which were categorized as conventional. These changes which have fundamental consequences are changing the scientific landscape, especially the branch of mass communication. As an umbrella scientific discipline that studies mass media, mass communication is also developing. The various consequences of these developments ultimately relate to theory and methods which are also developing but are relevant to current trends and directions in mass media. Even though some have been categorized and formulated in theory, along with trends, new theories are needed in accordance with developments that occur. In this regard, this research aims to determine the direction of media which is experiencing fundamental changes towards a more convergent direction that reaches other scientific disciplines. By using qualitative methods with careful observation, several things were discovered regarding the possibility of theoretical postulations by combining other scientific disciplines in their understanding which could touch directly on the scientific dimension.Keywords: Mass Communication, Mass Media, Communication Science